A Review Paper on Wireless Network - pal, Gajender; kumar, Kuldeep; kumar, Manish; GGN, DCE (IJRDO -Journal of Computer Science Engineering, 2015)
The arrival of wireless technology has reduced the human efforts for accessing data at various locations by replacing wired infrastructure with wireless infrastructure and also providing access to devices having mobility.Since wireless devices need to be small and bandwidth constrained, some of the key challenges in wireless networks are Signal fading, mobility, data rate enhancements, minimizing size and cost, user security and (Quality of service) QoS